FAKTOR PENGEMBANGAN DAN ISU DALAM MASALAH KARIER PUSTAKAWAN - Masriyatun Masriyatun (Jurnal Pustaka Ilmiah, 2015)
Human resource development is the personnel development activities in order to meet the desired career plan. Librarians in the organization of the library is expected to develop its potential. For that, it takes several factors in the career development of librarians and can not be denied that there will be issues in it. For development factors, including 1) fairness in career librarians; 2) care and supervision of a body builder; 3) awareness of career opportunities; 4) interest librarian; 5) librarian career satisfaction. While the issues in the career development of librarians, among them 1) membership librarian; 2) doubt in promotion; 3) the enforceability of the career development of librarians; 4) career opportunities for librarians; 5) diversity librarian position; 6) promotion of librarians; 7) the organization’s commitment to a career librarian.